Natalizumab in Multiple Sclerosis Treatment: From Biological Effects to Immune Monitoring - Khoy, Kathy; Mariotte, Delphine; Defer, Gilles; Petit, Gautier; Toutirais, Olivier; Le Mauff, Brigitte (Frontiers in Immunology, 2020)
Multiple sclerosis is a chronic demyelinating disease of the central nervous system (CNS) with an autoimmune component. Among the recent disease-modifying treatments available, Natalizumab, a monoclonal antibody directed against the alpha chain of the VLA-4 integrin (CD49d), is a potent inhibitor of cell migration toward the tissues including CNS. It potently reduces relapses and active brain lesions in the relapsing remitting form of the disease. However, it has also been associated with a severe infectious complication, the progressive multifocal leukoencephalitis (PML). Using the standard protocol with an injection every 4 weeks it has been shown by a close monitoring of the drug that trough levels soon reach a plateau with an almost saturation of the target cell receptor as well as a down modulation of this receptor. In this review, mechanisms of action involved in therapeutic efficacy as well as in PML risk will be discussed. Furthermore the interest of a biological monitoring that may be helpful to rapidly adapt treatment is presented. Indeed, development of anti-NAT antibodies, although sometimes unapparent, can be detected indirectly by normalization of CD49d expression on circulating mononuclear cells and might require to switch to another drug. On the other hand a stable modulation of CD49d expression might be useful to follow the circulating NAT levels and apply an extended interval dose scheme that could contribute to limiting the risk of PML.